KECERDASAN INTERPERSONAL HUMANISTIK DALAM PERSPEKTIF AL-QUR’AN - Al Firdaus (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2019)
From the explanation, the analysis of data processing that is carried out on humanistic interpersonal intelligence in the perspective of the Qur’an with the presentation of the chapters can be concluded as follows. The interesting thing which founded in this study is humanistic interpersonal intelligence is divided into two types; Internal and External. First, internal contains of: a. Positive replication of people with special needs, which is explained in the Surah ‘Abasa/80:1-4, b. Not hurting by hands, which is contained in Surah Al-Lahab/111:1-5 and Surah Al-Humazah/104: 1-2, c. Sharing advice, which is explained in Surah Al-‘’Ashr/103: 1-3, d. Intellectual sensitivity, which is found in Surah Al-‘Alaq/96:1-7, e. Not Over Confidence, which is written in surah Al-Hujarat/49:10-13, f. Effective dialogue education, which is written in Surah Luqman/31: 12-19, g. Intelligence dialogue education, in Surah Maryam/19:41-46, h. Believe in God (Allah), which is listed in Surah Al-Ikhlas /112:1-3. Second, External contains of: a. Maintaining tolerance, which is explained in Surah Al-Kafirun/109: 1-6, b. Not excessive, simple is better, which is explained in Surah At-Takastur/102:1-2, c. Maintaining faith and security, which is explained in Surah Quraisy/106:1-4, d. Maintaining healthy dialogue, which is found in Surah Thaha/20: 41-44. Third, humanistic interpersonal intelligence can be applied to Islamic education. Which emphasizes aspects of dealing with others widely. Not only at the theoretical level but also at the practical level can be applied with early learning. It is because the true purpose of education is to teach others to do well to all. Fourth, if humanistic interpersonal intelligence is implemented by people, it will be lead to compound tranquility or Rahmatan lill’alamiin for themselves and their surrounding. The method used in this study is descriptive and contextual analysis, while the approach used is a qualitative approach.